Keragaman Genetik Sirih Cina (Peperomia pellucida L.) Berdasarkan Penanda RAPD (Random Amplified Polymorphic DNA) - Nandariyah, Nandariyah; Ningsih, Hardian; Fadhillah, Annisa Nur; Parjanto, Parjanto; Paryanto, Edi (Agrosains : Jurnal Penelitian Agronomi, 2024)
Chinese betel is a plant widely found in Indonesia, especially in the ex-Karasidenan area of Surakarta. The existence of growing Chinese betel can be found at various altitudes with humid growing conditions with low sun intensity. People in Surakarta believe that Chinese betel can be used as a traditional medicine. Chinese betel nut is suspected to contain a minerals and bioactive substances that are beneficial to health. Currently, there are few references to Chinese betel, especially related to genetic diversity. This study aims to study the diversity of Chinese betel band patterns based on RAPD markers using OPA-3, OPA-4, OPA-11, OPC-05, and OPD-4 primers. This research was carried out at the Plant Breeding Laboratory, Faculty of Agriculture, Gadjah Mada University, Yogyakarta in July - November 2023 using Chinese betel leaf DNA taken from various places in the ex-karasidenan area of Surakarta. The results of the data analyzed by NTSYSpc version 2.02 with the SimQual (Similarity for Qualitative Data) function using the UPGMA (Unweighted Pair Group with Arithmetic Averaging) method based on the Jaccard similarity index value. The amplification results showed 30 bands with 13 polymorphic bands and 17 monomorphic bands. The level of polymorphism among Chinese betel samples in the five RAPD primers used presented 44.36% of the total 13 polymorphic bands. Jaccard's genetic similarity matrix data ranged from 0.667 – 0.964. The results of the dendogram show that the sample is divided into two clusters with a diversity index of 0.28.